MEANS OF DRUG DELIVERY IN THE EVENT OF INHALATION THERAPY IN CHILDREN: SELECTION CRITERIA - L. R. Selimzyanova (Pediatričeskaâ Farmakologiâ, 2014)
Inhalation therapy as means of drug delivery is a key aspect of therapy of respiratory diseases in children, which plays an important role in achieving control over bronchial asthma. Optimal clinical effect requires comprehensive selection of inhalation devices given the drug’s peculiarities, the child’s age, severity of his/her condition, the patient’s cognitive potential and capabilities of his/her parents, as well as clinical recommendations on the corresponding diseases. It is rather important to observe individual approach and the patient’s preferences in order to ensure adherence to the recommendations. One of the crucial conditions of effective inhalation therapy is a clear explanation of the inhalation technique and device maintenance by the doctor, as well as regular medical control over observation of the given instructions by the patient and his/her parents. The article presents an algorithm of selecting means of inhalation drug delivery for use in children and the review of currently marketed inhalers, their advantages and drawbacks.